Optimal modulation of a Brownian ratchet and enhanced sensitivity to a weak external force - Tarlie, Martin B. (National Academy of Sciences, 1998)
We studied the dynamics of a Brownian particle moving in a spatially anisotropic potential acted on by multiplicative temporal modulations so that V(x,t) = g(t)U(x). Using the concept of the “thermodynamic action,” we show that the class of modulation that maximizes the flow is a square-wave in time. We also show that adding a weak, homogenous force F in synergy with the square-wave modulation can cause particles of slightly different size to move in opposite directions. The synergetic change in velocity caused by F can be much greater than the drift velocity that would be caused by F alone.